Uji Potensi Senyawa Bioaktif Ekstrak Antosianin Jagung Ungu sebagai Inhibitor Cyclin-Dependent Protein Kinase 6 (CDK6) - Ayu Tri Agustin; Anas Fadli Wijaya (Jurnal Kesehatan Amanah, 2023)
Cancer is characterized by uncontrolled cell proliferation. The upregulation and activation of the Cyclin-Dependent Protein Kinase 6 (CDK6) signaling pathway can induce unregulated breast cancer cell proliferation. Therefore, CDK6 inhibition continues to be developed as a potential target for drug design and development to treat breast cancer. This study aims to predict the biofunction of anthocyanin compounds from purple corn extract as inhibitors of Cyclin-Dependent Protein Kinase 6 (CDK6) using an in silico approach. The research methods included data mining, ligand and receptor preparation, molecular docking, docking visualization, and data analysis. Our results indicate that six compounds from purple corn extract (cyanidin, cyanidin 3-glucoside, pelargonidin-3-glucoside, pelargonidin, peonidin, and peonidin-3-glucoside) can bind to CDK6 at the C-terminal and N-terminal domains. The binding pattern suggests that cyanidin, cyanidin 3-glucoside, pelargonidin-3-glucoside, pelargonidin, peonidin, and peonidin-3-glucoside interact with CDK6 residues in the same manner as Palbociclib (control). This finding indicates that compounds from purple corn have the potential to act as competitive CDK6 inhibitors. Peonidin-3-glucoside exhibited the lowest binding energy of -282.5 kcal/mol, approaching that of Palbociclib (-329.4 kcal/mol).